1950
DOI: 10.1177/003591575004300326
|View full text |Cite
|
Sign up to set email alerts
|

Periarteritis Nodosa

Abstract: 161 inches. X-ray of the skull is normal and shows orbits of normal size. Beyond the eye condition, which is as described above, examination reveals only a small hemangioma in the right pubic region and pallor of mucous membranes (R.B.C. 5,000,000 per c.mm.; Hb 6-6 gramme per 100 c.cm. (48 %); C.I. 0-49). Blood Wassermann negative. This is a case of bilateral retrolental fibroplasia in a premature small baby, complicated by general failure to thrive, anxmia, feeding difficulty and marked delay in behaviour dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The reactive bone is highly vascularized and contains fine cancellous tissue composed of irregular and radial spicules. Interestingly, there is more porous space but with overall lesser bone density than in the mammal-like response of the gorgonopsian (a phenomenon that has been noted previously in reptilian and amphibian reactive bone growth; [32]). Notably, the collections-based survey of wild and captive reptiles by Rothschild [29] showed that, while rare in non-mammals, non-traumatic osseous changes are more common in some reptile groups than in others.…”
Section: (B) Other Cases Of Non-mammalian Subperiosteal Haematomamentioning
confidence: 64%
See 1 more Smart Citation
“…The reactive bone is highly vascularized and contains fine cancellous tissue composed of irregular and radial spicules. Interestingly, there is more porous space but with overall lesser bone density than in the mammal-like response of the gorgonopsian (a phenomenon that has been noted previously in reptilian and amphibian reactive bone growth; [32]). Notably, the collections-based survey of wild and captive reptiles by Rothschild [29] showed that, while rare in non-mammals, non-traumatic osseous changes are more common in some reptile groups than in others.…”
Section: (B) Other Cases Of Non-mammalian Subperiosteal Haematomamentioning
confidence: 64%
“…The healing response appeared to be relatively rapid, with highly vascularized radial bone formation, thus necessitating comparisons to similar pathologies in nonmammals, such as varanids and crocodylians, where the tissue-level processes are not as well understood. At the moment, it is apparent that healing responses of ossifying haematomas may be somewhat conserved across tetrapods, while also being variable in the rate and extent of reactive bone formation during the ossification phase [32]. Further conclusions regarding synapsid physiology, however, will require additional baselines from other fossil and extant non-mammals.…”
Section: Discussionmentioning
confidence: 99%